The Administrative Contract and the Public Tender - Fernández Ruiz, Jorge (2015)
To achieve its goals, the State requires the voluntary collaboration of individuals, which takes form of an administrative contract, whose award is often disrupted by administrative corruption. Public tendering stands out among the mechanisms to prevent and fight administrative corruption in the award of administrative contracts.